Odpowiedzi

Najlepsza Odpowiedź!
2009-11-10T11:37:24+01:00
A) 2y+5x=6/*(-3)
3y+4x=7 3/4/*2

{ -6y -15x=-18
{6y +8x=31/2 dodajemy r-nia

-6y+6y-15x+8x=-18+31/2
-7x= -5/2/:(-7)
x= 5/14≈0,3
2y +25/14= 6 /*14
28y+25= 84
28y= 84-25
28y=59
y=59/28≈2,1
b) 2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

{ 7x+7y=42/:7
{-11x+23y=-32

{ x+y=6 czyli x=6-y
{-11*(6-y)+23y=-32
-66+11y+23y=-32
44y=-32+66
44y= 34/:44
y =17/22≈0,77
x=5,23
c)x+y pod kreska ulamkowa 3,+ y pod kreska ulamkowa 5=-2
2x-y pod kreska 3, - 3x pod kreska 4= 1.5

{ x+y/3 +y/5=-2/*15
{ 2x-y/3 -3x/4=1,5/*12

{ 5x+5y+3y=-30
{8x-4y-9x= 18

{5x+8y=-30
{-x-4y=18 czyli -x=18+4y stąd x= -18-4y

{ 5*(-18-4y)+8y=-30
- 80-20y+8y=-30
-12y=50/:(-12)
y= -4,16
x= -18+16,6=-1,4


2009-11-10T17:00:18+01:00
B) 2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
x+15y-16x+8y=-32

7x+7y=42
-15x+23y=-32

7x=42-7y /:7
-15x+23y=-32

x=6-y
-15(6-y)+23y=-32

x=6-y
-90+15y+23y=-32

x=6-y
38y=-32+90

x=6-y
38y=58/:38

x=6-y
y=58/38

x=6-58/38
y=58/38

x=228/39 - 58/38
y=58/38

x=170/38
y=58/38